DEVELOP THE ABILITY TO RECOGNIZE ABC-ABC PATTERNS USING PROBLEM-BASED LEARNING AND MAZE PATTERN GAMES IN CHILDREN AGED 4-5 YEARS - Siska Rianis Ardawati; Maimunah Maimunah (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2026)
The ability to recognize patterns repeatedly is important for every child. This study aims to describe teacher activities, children's activities, and the results of children's cognitive development to recognize the ABC-ABC pattern using the Problem Based Learning model through Maze Pattern Games activities. This study uses a qualitative approach with the type of Class Action Research (PTK) which was carried out in four meetings. The subjects of the study were 14 children of group A of Bakti 1 Islamic Kindergarten 1 Banjarmasin. Data collection uses observation techniques and assessments of teacher activities, children's activities, and children's cognitive development outcomes. Data analysis uses qualitative descriptive analysis in the form of tables and percentage graphs presented with established success indicators. The results showed that the teacher's activity in meeting 4 reached a score of 28 with the criteria of Excellent, in the children's activity in meeting 4 reached 100% with the category of All Active Children, and the achievement of classical child development in meeting 4 reached 100% with the criterion of Very Good Development. Based on the results of the data analysis, it can be concluded that the PBL model through the maze pattern play can be used as an effective learning reference in getting to know the ABC-ABC poa in children